The oxygen-bearing geolipids in the Lucaogou shale of Upper Permian, Santanghu Basin, China. (December 2016) - Wang, Zuodong; Liang, Mingliang; Qian, Yu; Wang, Zhiyong; Li, Xiaobin; Li, Zhongping
Highlights: We report several oxygenated geolipids from a Permian shale for the first time. These include C8 –C27 γ-butyrolactones and C8 –C25 δ-valerolactones. The major precursors of these compounds are thought to be from microalgae. They are probably formed from the transformation of organic matter by bacteria. Abstract: An abundant series of C8 –C27 γ- n -alkyl-γ-butyrolactones, γ-isoprenoid-alkyl-γ-butyrolactones with side chains consisting of 1–3 isoprenoid units, and C8 –C25 δ- n -alkyl-δ-valerolactones were identified in the Upper Permian shale of the Lucaogou Formation of the Santanghu Basin (270–250 Ma) in eastern Xinjiang, China. The possible origin of these compounds is discussed, particularly of those which had not been identified previously as geolipids in Permian rocks. Contributions from microalgae such as eustigmatophytes and transformation of organic matter by bacteria were likely sources of these oxygen-bearing geolipids.